2018
DOI: 10.1016/j.jval.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Does Inclusion of Interactions Result in Higher Precision of Estimated Health State Values?

Abstract: Background: Most preference-based instruments producing overall values for health states are devised on the simplifying assumption that the overall effect of distinct health-related quality of life domains (attributes) of the instrument equals the sum of the attributes. Nevertheless, health attributes are often inter-related and depend on each other. Objectives: To investigate whether inclusion of secondorder interactions in the three-level EuroQol five-dimensional questionnaire (EQ-5D-3L) value function would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Results are shown in Table 1 in the supplementary material. Similar to the findings of Nicolet et al (2018), we found that including all two-way interaction effects slightly improved model fit [ 36 ]. In the interaction model, it is important to refrain from interpreting isolated main effects from interaction effects, as such interpretations can be misleading.…”
Section: Resultssupporting
confidence: 89%
“…Results are shown in Table 1 in the supplementary material. Similar to the findings of Nicolet et al (2018), we found that including all two-way interaction effects slightly improved model fit [ 36 ]. In the interaction model, it is important to refrain from interpreting isolated main effects from interaction effects, as such interpretations can be misleading.…”
Section: Resultssupporting
confidence: 89%
“…This seemed reasonable, because it is commonly used to represent health state preferences -most EQ-5D-5L value sets are based on such a model. When studies test for and include interaction effects, authors also often find only minor improvements in the explanatory power 35 .…”
Section: Discussionmentioning
confidence: 99%
“…A multiplicative interaction term between injection device type and frequency of injection was included in the model as these two attributes were hypothesized to be conceptually related (eg, preference for the frequency of injections may vary depending upon the type of injection device); in such cases, interaction terms are recommended. 14,15 Regression coefficients were also used to assess the relative importance of treatment attributes in participants' preference decisions among all attributes and among attributes that were significantly associated with treatment preference. To facilitate the interpretation, the relative importance of treatment efficacy outcomes was quantified as follows: 60% reduction in the frequency of severe asthma attacks (an efficacy estimate found in clinical trials) 16,17 and 250 mL improvement in lung function (an improvement that is considered moderately better by patients).…”
Section: Discussionmentioning
confidence: 99%
“…A multiplicative interaction term between injection device type and frequency of injection was included in the model as these two attributes were hypothesized to be conceptually related (eg, preference for the frequency of injections may vary depending upon the type of injection device); in such cases, interaction terms are recommended. 14 , 15 …”
Section: Methodsmentioning
confidence: 99%